Associação entre transtorno do espectro autista e doença cárie: estudo de casocontrole - Keller, Alexandra Oliveira (2020)
Autism Spectrum Disorder (ASD) is a condition of increasing prevalence that requires investments by the public health system. Participants with ASD present difficulties in communication and social interaction as main characteristics and may present a higher risk of caries, particularly due to difficulties in oral hygiene and changes in eating patterns. The aim of this study was to evaluate the association between ASD and caries, as well as oral hygiene habits and eating patterns. A case control study was conducted, whose cases were 40 participants with ASD (5 to 15 years of age), matched by gender and age (+/- 2 years) with 40 participants without ASD. Both were recruited in the municipalities of Passo Fundo, Erechim, Veranópolis and Venâncio Aires. The outcome caries was quantified after dental clinical examination, using the indexes ceod and CPOD. The odds ratio of the association between ASD and caries was calculated. The software used for statistical analysis was Stata 14.0®. The main results are that the presence of caries did not differ between cases and controls (p=0.823), with no association between ASD and caries (odds ratio: 0.81 (0.31 – 2.15)). However, the consumption of sugary foods was lower in participants with ASD (p=0.046), and it can be interpreted that they eat less sweets because they have a diet more supervised by their caregivers. Among 40 participants with ASD 58% had the help of a person responsible for oral hygiene, while 87% of the controls performed alone (p=0.001). Regarding the abandonment of dental treatment, 30.8% of participants with ASD have already abdicated, without completing the procedures in the service sought, but only 8.9% of the controls. We can conclude that the frequency of caries does not differ between cases with ASD and controls without ASD, despite inequalities in oral hygiene and feeding patterns. The data obtained suggest that although the greater difficulty in oral hygiene in individuals with ASD, there may be compensation with greater care of those responsible and monitoring of eating patterns.